An Efficient Synthesis of Aryl-Substituted Pyrroles by the Suzuki–Miyaura Coupling Reaction of SEM-Protected Pyrroles - Keli Cui (Molecules, 2019)
An efficient arylation of SEM-protected pyrroles by the Suzuki–Miyaura coupling reaction has been developed. The reaction can be carried out under mild conditions to provide aryl-substituted pyrroles in moderate to excellent yields. The scope and limitations of the methodology were evaluated, and the reaction was tolerant of a wide range of functionalities. Compared to the reported methods, the protocol has some advantages, such as commercially available materials, no debrominated by-products being formed, and the amine-protecting group being stable under the reaction conditions. The synthetic utility of the product has also been demonstrated, with several common transformations of the aryl-substituted pyrrole product being conducted. This protocol will offer the opportunity to explore other metal-catalyzed cross-coupling reactions employing SEM-protected pyrroles.